Small needle decompression is equally effective like chest drain in a case of massive pneumothorax: a case report - Bhowmik, Dr.Amit (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
A 64 yrs,male patient presented with sudden onset of respiratory distress for which he was admitted in some other hospital.The symptoms were mild there on presentation which increased gradually and he was shifted to Glocal hospital, Krishnanagar for further management. The patient had a recent history of hospitalization in the same hospital for LRTI, urosepsis and arrhythmia. He is also a case of Ca-urinary bladder. He was recovered from the respiratory infection with a residual cough during the last visit.